Unsurpassed Intrahepatic Islet Engraftment – the Quest for New Sites for Beta Cell Replacement. (24th June 2019) - Liljebäck, Hanna; Espes, Daniel; Carlsson, Per-Ola
The liver is currently the site of choice for clinical islet transplantation, even though many alternative implantation sites have lately been proposed as more ideal for graft survival. The suggested sites, for example intramuscular space, omentum, bone marrow, and spleen, are sometimes difficult to compare due to differences in animal model, islet isolation procedure, and islet quality. In addition, the variation in transplanted islet mass is vast. The aim of this commentary is to review alternative implantation sites tested experimentally as well as in clinical islet transplantation. Although many sites have been investigated, none have convincingly proved better suited for clinical islet transplantation than intraportal injection to the liver, regardless of whether it is autologous or allogeneic transplantation. However, in order to fully evaluate upcoming bioengineering techniques, such as scaffolds containing insulin-producing cells derived from stem cells, the need of an alternative site has arisen to enable cellular monitoring, which currently cannot be achieved within the liver.